Barriers to the Implementation of Shared Micro-Mobility Services in a Highly Motorized Context - Khankhokkruad, Worakanya; Boonsiripant, Saroch; Jittrapirom, Peraphan (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
Shared Micro-Mobility (SMM) services are a popular sustainable alternative to private vehicle use globally, particularly in European and Western cities, offering flexible, cost-effective, and on-demand transportation for short-distance trips and as a first/last-mile service. However, implementing SMM services in developing countries faces challenges, such as poor road conditions, private mode habits, and lack of connectivity. This research examines factors hindering SMM implementation and operation in Bangkok, Thailand, using a combination of a Systematic Literature Review (SLR) and stakeholder interviews. The SLR approach used a keyword-based search to identify relevant articles and applied stringent criteria to exclude irrelevant ones. Subsequently, further articles were sourced to complement the selected ones. For stakeholder interviews, a total of 33 stakeholders related to the implementation of SMM services in Bangkok, including researchers, government agencies, and service providers, were included. The study found 53 potential barriers to implementing SMM in Bangkok, including 35 from stakeholder interviews and 34 from the literature review. After filtering out duplicates and irrelevant barriers, 26 barriers were identified and categorized into six groups including User Barriers, Institutional and Governance Barriers, City Infrastructure Barriers, Technological Barriers, Geographical Barriers, and Operational Barriers. The findings of this research can assist practitioners and decision-makers in formulating planning policies that can address the challenges facing the implementation of SMM services in both developing countries and Bangkok. SMM service providers can also utilize the findings to improve the service’s operation and implementation.